#### Answer

(4,3)

#### Work Step by Step

Multiply the second equation by -1. Add the equations to eliminate y.
$6x+5y=39\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 6x+\ 5y=\ \ \ 39$
$3x+5y=27\ \ \ \ $multiply by -1$\ \ \ \ \ \ \ \ \ \ \ \underline{\ -3x-5y=-27}$
$\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 3x\ \ \ \ \ \ \ \ \ =\ \ 12$
Solve for x.
$3x=12$
$3x\div3=12\div3$
$x=4$
Substitute 4 for x in either equation and solve for y.
$6(4)+5y=39$
$24+5y-24=39-24$
$5y=15$
$5y\div5=15\div5$
$y=3$